Due process as a limit to discretion in international commercial arbitration - Ferrari, Franco, 1965-; Rosenfeld, Friedrich (Friedrich Jakob); Czernich, Dietmar (Kluwer Law International B.V., 2020)
The absence of a coherent body of case law on due process has increasingly motivated recalcitrant parties to use due process as a strategic tool, thereby putting at risk the prospect of obtaining an enforceable award in expeditious proceedings. Countering this inherent danger, here for the first time is a comprehensive study on due process as a limit to arbitral discretion, showing how due process applies in practice in key jurisdictions around the world. Based on country reports prepared by leading arbitration practitioners and academics, the book explores how courts in major arbitration jurisdictions apply due process guarantees when performing their post-award review.